Southern Sandbur (Cenchrus echinatus L.) Control in Bermudagrass Pastures with Indaziflam Herbicide Systems (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Field studies were conducted during 2019 growing season in north-central, south-central, and the Coastal Bend areas of Texas to evaluate indaziflam herbicide systems for southern sandbur control and Coastal bermudagrass tolerance.  Indaziflam caused no bermudagrass stunting at any location when applied preemergence (PRE) at 0.04 to 0.07 kg ai ha-1.  Glyphosate at 0.35 kg ae ha-1 caused bermudagrass stunting which ranged from 16 to 65% when evaluated 3 to 5 weeks after application; however, when evaluated at the end of the growing season, no bermudagrass stunting was evident when compared with the untreated check.  Southern sandbur control with indaziflam, when evaluated 28 to 32 weeks after the initial indaziflam PRE application, ranged from 85 to 99% in north-central Texas, 65 to 95% in south-central Texas, and 95 to 100% in the Coastal Bend region.  Southern sandbur control with pendimethalin PRE system ranged from 74 to 100%, 11 to 85%, and 100% in those regions, respectively.  Indaziflam represents a safe option for forage and hay producers in Texas to control southern sandbur.